The Potential of Tubing Ecotourism for the Empowerment of Kali Pucung Kemuning Community - Leonardo Mada Sulistyanto; Setya Rahayu (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2025)
Ecotourism is a form of tourism that prioritises the principle of sustainability by utilising natural resources and involving the active participation of local communities. The Pucung River in Kemuning, Karanganyar Regency, possesses natural resources and potential that support its development as a tubing ecotourism destination capable of improving the welfare of the local community. This study aims to analyse the potential of tubing ecotourism for community empowerment. The research method employed a quantitative descriptive approach. Data were collected through observation, interviews, and documentation of data sources with ecotourism managers, the local community, and visitors to the Kali Pucung Tubing ecotourism site. The results indicate that ecotourism tubing at Kali Pucung holds high potential in terms of natural appeal, community participation, and economic opportunities. This opens up strategic opportunities for targeted training and mentoring for the local community regarding sustainable tourism management. The findings of this study indicate that the development of tubing ecotourism not only contributes to the growth of the local tourism sector but is also capable of promoting community empowerment both economically and socially. In conclusion, Tubing Kali Pucung ecotourism has the potential to become a flagship sector that increases tourist visits and drives the economic empowerment of the local community.